Assessment of 53Mn deposition on Earth via accelerator mass spectrometry. (October 2018) - Rodrigues, Darío; Negri, Agustín E.; Balpardo, Christian; Arazi, Andrés; Faestermann, Thomas; Fernandez Niello, Jorge O.; Fimiani, Leticia; Gómez Guzmán, José Manuel; Hain, Karin; Korschinek, Gunther; Ludwig, Peter; Marti, Guillermo V.
Abstract: The 53 Mn flux onto Earth is a quantity relevant for different extraterrestrial and astrophysical questions. It is a proxy for related fluxes, such as supernova-produced material or interplanetary dust particles. In this work, we performed a first attempt to assess the 53 Mn flux by measuring the 53 Mn/ 10 Be isotopic ratio in a 1400 L sample of molten Antarctic snow by AMS (Accelerator Mass Spectrometry). Using the 10 Be production rate in the atmosphere, an upper limit of 5.5 × 10 3 atoms cm −2 yr −1 was estimated for the deposition of extraterrestrial 53 Mn. This result is compatible with one of the two discrepant values existing in the literature. Highlights: A novel approach to assess the 53 Mn deposition on Earth is proposed. 1400 l of snow from Antarctica were chemically processed to extract Mn and Be. 53 Mn/ 55 Mn and 10 Be/ 9 Be isotope ratios were measured by accelerator mass spectrometry. An upper limit for the 53 Mn global flux is established.